Detection of Adenoviruses from clinical samples in bone marrow transplant patients by nested PCR (polymerase chain reaction) - Sabagh, Fatemeh; Roggendorf, Michael (Archives of Advances in Biosciences, 2012)
Adenoviruses are recognized as common human pathogens that are responsible for a wide variety of infectious syndromes. Bone marrow transplant patients are prone to life threatening opportunistic infections like adenoviruses. The nested polymerase chain reaction has provided an alternative, sensitive diagnostic method for detection of Adenoviruses. In this study we developed PCR from hexon genes as rapid diagnostic method of Advs infections on different clinical samples. Adenovirus infections was defined as the presence of DNA in the blood, urine, stool, or respiratory lavage from bone marrow transplant patients. Two sets of primers (Group specific primers and internal primers) were required to optimize the PCR protocol. This highly sensitive method could detect different types of Advs in two separate sets of PCR. Therfore,DNA amplification in BMT patients would be valuable screening way to evaluate bone marrow transplant recipients. Early detection of Advs by PCR assay is important to asymptomatic infections or preventing aggressive antiviral thearapy.